Analysis of peptide antibiotic residues in milk using liquid chromatography-high resolution mass spectrometry (LC-HRMS). Issue 8 (2nd August 2020) - Wu, I-Lin; Turnipseed, Sherri B.; Andersen, Wendy C.; Madson, Mark R.
ABSTRACT: A liquid chromatography-high resolution mass spectrometry (LC-HRMS) method was developed and validated for the determination of residual peptide antibiotics (bacitracin A, colistin A and B, enramycin A and B, virginiamycin M1 and S1) in bovine milk. LC-HRMS accurate mass data provided the necessary selectivity and sensitivity to quantitate and identify these important antibiotics in milk at residue levels without extensive sample preparation. Milk samples were extracted using 0.3% formic acid in acetonitrile with 0.06% trifluoroacetic acid added to improve peptide recoveries. Sample clean-up was minimal with an aliquot of the extract evaporated and reconstituted in a formic acid/water-acetonitrile mixture and then filtered. LC separation was performed with 0.3% formic acid in the gradient to improve the peak shape and reproducibility of the peptide analytes. A Quadruple-Orbitrap HRMS instrument with full-scan MS1 data collection followed by all-ion-fragmentation was used to obtain the exact mass of the precursor and confirmatory product ions. One advantage of LC-HRMS is that a combination of multiple precursor ions, including different charge states or adducts, can be used for quantification. The method was validated at four concentration levels ranging from 12.5 to 200 ng/g in three types of bovine milk. For bacitracin A, colistins and enramycins, the average recoveries compared to solvent standards ranged between 70% and 120%. Average recoveries for virginiamycin residues in milk extracts were unacceptably high (up to 138%) using solvent standards, but recoveries using matrix-matched calibration were determined to be 90–115%. Matrix effects were found to be less than 25% for the other analytes when internal standard correction was used for the colistins. Intra-day relative standard deviations were generally below 15%. The method detection limits for the peptide antibiotic residues in milk (0.5 to 5.5 ng/g) were well below regulatory levels of concern. Graphical Abstract: